Dynamics of a Tidal Current System in a Marginal Sea: A Case Study of the Yellow Sea, China - Zhang, Qian; Su, Min; Yao, Peng; Chen, Yongping; Stive, Marcel J. F.; Wang, Zheng B. (Frontiers in Marine Science, 2020)
Tidal currents belong to the main driving forces shaping the bathymetry of marginal seas. A globally unique radial sand ridge field exists in the South Yellow Sea off the central Jiangsu coast, China. Its formation is related to the distinctive “radial tidal current” pattern at that location. A generally accepted hypothesis is that the “radial tidal current” is a consequence of the interference between the northern amphidromic tidal wave system and the southern incoming tidal wave. In this study, a schematized numerical tidal model was designed to investigate the tidal current system and the factors of influence in the South Yellow Sea. Concepts of the tidal current amphidromic point (CAP) and the tidal current inclination angle are utilized to analyze the inherent structure of the tidal current system. By conducting a series of numerical experiments, it is found that the Poincaré modes are necessary for the existence of “radial tidal current,” and the e-folding decay length should be smaller than the basin length. In the Yellow Sea, cross-basin phase differences due to lateral depth differences as well as open boundary conditions favor the emergence of the “radial tidal current.” Further analyses indicate that the CAP system (i.e., the co-inclination lines, the CAPs, and the tidal ellipticity) deepens the understanding on the dynamic structure of a tidal current system, and therefore, it deserves more attention in future studies.